PERENCANAAN INSTALASI PIPA DISTRIBUSI AIR BERSIH DI DESA PIMPING KECAMATAN TANJUNG PALAS UTARA KABUPATEN BULUNGAN - Abadi, Jefri (KURVA S JURNAL MAHASISWA, 2014)
Clean Water is water which in using for the requirement of everyday human being and will become drinking water after cooked particularly its definition dahulu.Sebagai of clean water is water fulfilling conditions to conditions minum.Adapun water system which in intention is conditions from facet of is quality of water covering the quality of radiologis fisik, kimia, biologis, and so that if consumed is not dangerous or generate side effects to human being.Â Method used for the calculation of resident projection is with Method Aritmatik and Method Geometrik, while formula which is used in calculation of pipe is with formula equation of Hazen Williams.